Building Natural History Collections for the Twenty-First Century and Beyond. (15th July 2020) - Miller, Sara E; Barrow, Lisa N; Ehlman, Sean M; Goodheart, Jessica A; Greiman, Stephen E; Lutz, Holly L; Misiewicz, Tracy M; Smith, Stephanie M; Tan, Milton; Thawley, Christopher J; Cook, Joseph A; Light, Jessica E
Abstract: Natural history collections (NHCs) are important resources for a diverse array of scientific fields. Recent digitization initiatives have broadened the user base of NHCs, and new technological innovations are using materials generated from collections to address novel scientific questions. Simultaneously, NHCs are increasingly imperiled by reductions in funding and resources. Ensuring that NHCs continue to serve as a valuable resource for future generations will require the scientific community to increase their contribution to and acknowledgement of collections. We provide recommendations and guidelines for scientists to support NHCs, focusing particularly on new users that may be unfamiliar with collections. We hope that this perspective will motivate debate on the future of NHCs and the role of the scientific community in maintaining and improving biological collections.